Biología del género Melaloncha (Phoridae) moscas parasitoides de la abeja doméstica (Apis mellifera L.) en Costa Rica - Ramírez, William (1984)
Approximately eight species of the Phorid fly, Melaloncha, were seen parasitizing honey bees, especially during the rainy season in various parts of Costa Rica. Copulation of these flies takes place in the vicinity of the beehives and around flowers visited by both species. Melaloncha apparently introduces the ovipositor through the intersegmental membranes of the abdomen of the bee, where the first larval stages develop. After the bee dies, the larva migrates to the thorax where it completes its development and pupates. Melaloncha also parasitizes Bombus Mexicanus and Melipona fasciata. Parasitism of honey bees by this Phorid has serious economic implications.